Physical activity and high-intensity running during sided games vs. competitive match-play in elite soccer players: A comparative study - Payet, F.; Rouissi, M.; Chtara, M.; Colson, S.; Wong, D. P.; Owen, A. L.; Diaz-Cidoncha Garcia, J.; Chamari, K.; Dellal, A. (Journal of Novel Physiotherapies, 2016)
Aim: The aim of this study was to compare the physical activity of players within different sided games (SSG and LSG) and with those found among elite soccer match-play. Methods: Fourteen elite soccer players (age: 23.1 years; height: 178.4 cm; weight: 73.7 kg and body fat mass 8.8%) participated in 3 competitive matches and their data were compared to the following sided games: 5 vs. 5 and 6 vs. 6, 7 vs. 7, and 9 vs. 9. Total distances covered/min (TDC), TDC/min at high intensity running (between 16 and 23 km/h-1) and TDC/min at very high intensity running (>23 km/h-1) were analyzed during all SSGs and official match-play with GPS technology (15 Hz). Results: Post-hoc analysis indicated that the TDC/min was significantly higher during official match-play, 9 vs. 9, and 7 vs. 7 when compared to 6 vs. 6 and 5 vs. 5 (P<0.001). Moreover, the TDC/min, and the TDC/min at high and very high running intensity were significantly higher during the official match-play and large-sided games (9 vs. 9 and 7 vs. 7) than during the 6 vs. 6 and 5 vs. 5 SSG (P<0.001). Conclusion: The present study showed that physical activity, and especially at very high intensity running, was similar in official match-play and in LSG (9 vs. 9 and 7 vs. 7) whereas SSG (5 vs. 5 and 6 vs. 6) induced lower solicitations at the speed thresholds analyzed. In this context, SSG seems not allow to fully recreate the physical match-play demands with a specific difference for the high intensity running activities